The efficiency of the uterocervical angle in the prediction of second-trimester pregnancy terminations in multiparous women. (17th November 2019) - Aslan Cetin, Berna; Aydogan Mathyk, Begum; Koroglu, Nadiye; Demirezen, Gozde; Turan, Gokce; Demirayak, Gokhan; Yildirim, Gokhan
Abstract: Aim: To show how uterocervical angles are used for the prediction of second-trimester pregnancy terminations in multiparous women. Material and methods: A total of 148 multiparous singleton women in their second trimesters were enrolled in this prospective study. The intracervical Foley catheter was used for the induction of delivery. The cervical length (CL) and the uterocervical angle (UCA) were measured before the beginning of induction. The study population was subdivided into four groups; successful and failed terminations at the end of 24 and 48 h time frames. A stepwise multiple regression analysis was carried out to examine the contribution of UCA and other parameters to the induction-to-delivery time. A survival analysis was conducted to compare two groups defined by the cut-off value. Results: The UCA was broader in the successful termination group compared to the failed termination group in 24 h of induction (112.50° ± 29.00° versus 100.68° ± 27.13°, p  = .02). A negative correlation was found between the UCA and the induction-to-delivery time ( r  = −0.27, p  = .0007). A cut-off value of 97.5° was found for the UCA in predicting induction outcomes. During the 24-h period, 63.1% of women with the UCA ≥97.5° terminated successfully while 36.8% of women with the UCA <97.5° terminated successfully ( p  = .001). The mean induction-to-delivery time was significantly shorter in the UCA ≥97.5° group compared to the UCA <97.5° group (38.2 ± 19.5 h versus 47.8 ± 27.5 h, p  = .02). The binary logistic regression analysis showed that the UCA was the only contributor to a successful termination (OR = 1.01, 95% CI: 1–1.02, p  = .02). Conclusion: The UCA is broader in multiparous women who successfully terminated and is linked to a shorter duration of induction. The UCA by itself is the only significant contributor to the outcome of second trimester pregnancy terminations.